2018
DOI: 10.1016/j.cellsig.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1/p53 signaling in renal fibrogenesis

Abstract: Fibrotic disorders of the renal, pulmonary, cardiac, and hepatic systems are associated with significant morbidity and mortality. Effective therapies to prevent or curtail the advancement to organ failure, however, remain a major clinical challenge. Chronic kidney disease, in particular, constitutes an increasing medical burden affecting >15% of the US population. Regardless of etiology (diabetes, hypertension, ischemia, acute injury, urologic obstruction), persistently elevated TGF-β1 levels are causatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 157 publications
(201 reference statements)
6
99
0
Order By: Relevance
“…for p53 docking in a typical dimer-of-dimers configuration, are not separated by a nucleotide spacer (105,106). These data as well as the inclusion of PAI-1 as a member of the p53 target database, the topographic proximity of the p53 binding motifs to the transcription start site, the chromatin immunoprecipitation-confirmed p53 occupancy of the PAI-1 promoter, and the pharmacologic and genetic findings reviewed earlier (71,73) conclusively implicate p53 as a major cofactor in PAI-1 gene transcription.…”
Section: P53 Is Required For Expression Of a Subset Of Tgf-b1 Profibrsupporting
confidence: 65%
See 2 more Smart Citations
“…for p53 docking in a typical dimer-of-dimers configuration, are not separated by a nucleotide spacer (105,106). These data as well as the inclusion of PAI-1 as a member of the p53 target database, the topographic proximity of the p53 binding motifs to the transcription start site, the chromatin immunoprecipitation-confirmed p53 occupancy of the PAI-1 promoter, and the pharmacologic and genetic findings reviewed earlier (71,73) conclusively implicate p53 as a major cofactor in PAI-1 gene transcription.…”
Section: P53 Is Required For Expression Of a Subset Of Tgf-b1 Profibrsupporting
confidence: 65%
“…USF2 occupancy of the PAI-1 promoter proximal E box 2 (PE2) region E box (CACGTG) site, which adjoins the 3 59 SMAD binding elements (SBEs) that mediate TGF-b1induced gene expression ( Fig. 6A), is essential for the growth state-dependent transcriptional activation of the PAI-1 gene (71,(122)(123)(124). USF1 and -2 involvement in PAI-1 gene control has significant implications regarding both renal fibrosis and p53 function (124)(125)(126)(127)(128)(129)(130).…”
Section: Modeling P53-smad Interactions With Accessory Coactivatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive evidence demonstrated that fibrogenesis is associated with renin-angiotensin system, inflammation and oxidative stress, transforming growth factor β (TGF-β)/Smad signaling, Wnt/βcatenin signaling and lipid metabolism [1][2][3][4][5][6][7][8][9][10]. Among them, TGF-β/ Smad signaling plays an important role in fibrosis [1,[11][12][13][14]. Bona fide TGF-β is sequestered into the matrix in a latent state and must be activated before it can bind to its receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This review focuses on the action mechanism of TGF-β/Smad signaling pathway and its therapeutic intervention. In addition, we also discuss the effects of other intracellular factors including tumor necrosis factor receptor-associated factor 6, TGF-β-activated kinase 1, mitogenactivated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K), p53 and integrin on TGF-β/Smad signaling pathway [13,[20][21][22]].…”
Section: Introductionmentioning
confidence: 99%